Camera trapping on crocodile landing sites in Kuching Wetland National Park - Abdul Aziz Na'imullah, Zaidi (Universiti Malaysia Sarawak, (UNIMAS), 2015)
An assessment using camera traps was carried out in Kuching Wetland National Park from April 2014 to February 2015 to determine the activity pattern of the saltwater crocodile (Crocodylus porosus). In 799 camera traps days, two Bushnell Trophy Cam units and three Reconyx units captured a total of 106 photographs and recorded 6 videos comprising 13 photos of target species, Crocodylus porosus and additional photos of 11 species consist of Macaca fascicularis (29), Trachypithecus cristatus (4), Lutrogale perspicillata (18), Aonyx cinerea (16), Varanus salvator (10), Centropus sinensis (6), Actitis hypoleucos (1), Ixobrychus cinnamomeus (1), Copsychus saularis (1), unidentified rat (2) and unidentified squirrel (1). Four videos of Aonyx cinerea and 2 videos of Macaca fascicularis were recorded at the location CT 2. The number of photos captured was relatively high for crocodile during incoming high tide. Activity patterns were calculated for 4 species mainly for Crocodylus porosus as well as other 3 species possibly the prey species. The prey-predator relationship is discussed.